Reach out and grasp the opportunity: reconstructive hand surgery in tetraplegia. (May 2019) - Fridén, Jan; Lieber, Richard L.
Reconstructive upper extremity surgeries in tetraplegia are technically challenging because of the many complicated real-time decisions that need to be made, e.g. extent of release of donor muscle-tendon complex, routing of donor muscles, tissue preparation and optimization, tensioning of muscle-tendon units, balancing joints and suturing tendon-to-tendon attachments. Nerve transfer surgeries can add functionality but also make the reconstruction planning more complex. In this overview, we present some of the fundamental muscle-tendon-joint mechanics studies that allow for single-stage surgical reconstruction of hand function as well as early postoperative activity-based training in patients with cervical spinal cord injuries. We foresee an increased need for studies addressing combined nerve and tendon transfer reconstructions in parallel with patient-perceived outcome investigations. These should be combined with implementation of assistive technology such as functional electrical stimulation for diagnostic, prognostic and training purposes.